“Global” vs. “local”: Two readings of theoretical and methodological position of Branko Gavela - Vladimir D. Mihajlović (University of Belgrade, 2016)
The paper presents two possible readings of one discussion by Branko Gavela on the problems of protohistoric archaeology. From two distinct perspectives – one based upon the general pattern of development of archaeological thought, the other taking into account the specific local context, two disparate interpretations emerge of Gavela’s methodological conclusions. The general pattern of development of archaeological theory through three stages proves to be insufficient, and the author stresses the need to consider scholarly texts in the local context of the discipline. Instead of positioning Gavela’s texts as the “heralds” of theoretical changes in archaeology, a completely different position of his writings emerges, heavily influenced by the specific situation of archaeology in Serbia after the World War II.